Wealth effects of regulatory reform - Fields, Joseph A.; Ghosh, Chinmoy; Kidwell, David S.; Klein, Linda S. (Journal of Financial Economics, 1990)
This paper investigates the effect of California's Proposition 103 on the market value of publicly traded property- and liability-insurance companies. The passage of this referendum on November 8, 1988 moved California from a market-oriented to a heavily regulated insurance-pricing system. During the period surrounding the election, the average stock price of insurance companies doing business in California declined by 6.91%. The decline is positively related to the proportion of a firm's premiums affected by the referendum and the proportion generated in other states where insurance regulation is likely to change, and negatively related to the firm's profitability.